Technological and Thermal Properties of Thermoplastic Composites Filled with Heat-treated Alder Wood - Mürşit Tufan; Türker Güleç; Emrah Peşman; Nadir Ayrilmis (BioResources, 2016)
This study investigated the effect of heat-treated wood content on the water absorption, mechanical, and thermal properties of wood plastic composites (WPCs). The WPCs were produced from various loadings (30, 40, and 50 wt%) of heat-treated and untreated alder wood flours (Alnus glutinosa L.) using high-density polyethylene (HDPE) with 3 wt% maleated polyethylene (MAPE) coupling agent. All WPC formulations were compression molded into a hot press for 3 min at 170 ºC. The WPCs were evaluated using mechanical testing, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The mechanical property values of the WPC specimens decreased with increasing amounts of the heat-treated wood flour, except for the tensile modulus values. The heat treatment of alder wood slightly increased the thermal stability of the WPCs compared with the reference WPCs. The crystallization degree (Xc) and the enthalpy of crystallization of the WPCs slightly decreased with increasing content of the heat-treated wood flour. However, all WPCs containing the heat-treated alder wood flour showed a higher crystallinity degree than that of the virgin HDPE.